Microglial control of neuronal activity - Béchade, Catherine; Cantaut-Belarif, Yasmine; Bessis, Alain (Frontiers in Cellular Neuroscience, 2013)
Fine-tuning of neuronal activity was thought to be a neuron-autonomous mechanism until the discovery that astrocytes are active players of synaptic transmission. The involvement of astrocytes has changed our understanding of the roles of non-neuronal cells and shed new light on the regulation of neuronal activity. Microglial cells are the macrophages of the brain and they have been mostly investigated as immune cells. However recent data discussed in this review support the notion that, similarly to astrocytes, microglia are involved in the regulation of neuronal activity. For instance, in most, if not all, brain pathologies a strong temporal correlation has long been known to exist between the pathological activation of microglia and dysfunction of neuronal activity. Recent studies have convincingly shown that alteration of microglial function is responsible for pathological neuronal activity. This causal relationship has also been demonstrated in mice bearing loss-of-function mutations in genes specifically expressed by microglia. In addition to these long-term regulations of neuronal activity, recent data show that microglia can also rapidly regulate neuronal activity, thereby acting as partners of neurotransmission.